Effective part selection for part-based gait identification - Rokanujjaman, M.; Hossain, M. A.; Islam, M. R. (2012 7th International Conference on Electrical and Computer Engineering, 2012)
Different cofactors can affect different body parts and make difficulties for gait identification We study the contributions of very small segment in term recognition rate for dividing the body into five parts. Depending on the positive or negative effects for recognition, three parts are selected as effective parts and other two parts discarded as redundant. Experimental result shows promising performance in comparison with other part based methods.